2021
DOI: 10.3390/brainsci11040483
|View full text |Cite
|
Sign up to set email alerts
|

Null Effect of Transcranial Static Magnetic Field Stimulation over the Dorsolateral Prefrontal Cortex on Behavioral Performance in a Go/NoGo Task

Abstract: The purpose of this pilot study was to investigate whether transcranial static magnetic field stimulation (tSMS), which can modulate cortical excitability, would influence inhibitory control function when applied over the dorsolateral prefrontal cortex (DLPFC). Young healthy adults (n = 8, mean age ± SD = 24.4 ± 4.1, six females) received the following stimulations for 30 min on different days: (1) tSMS over the left DLPFC, (2) tSMS over the right DLPFC, and (3) sham stimulation over either the left or right D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…The mean error ratios are presented in Table 2 . No statistical test was performed for the error ratios because most participants made no or few errors [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean error ratios are presented in Table 2 . No statistical test was performed for the error ratios because most participants made no or few errors [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each task was performed using two different signal presentation devices: an LED lighting device (Light condition) and an LCD monitor (Monitor condition). In the Light condition, a custom-made LED lighting device (4 Assist, Tokyo, Japan) was used to present blue and red lights [ 21 ]. Red and blue LED bulbs were placed close to each other, and these lights were visible from one spot through a hole (5 mm) created in the device.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work investigating the potential of tSMS for modulating DLPFC function has yielded varied results. For example, Watanabe et al (2021) observed that applying tSMS for 30 minutes over the left DLPFC did not affect performance in a Go/noGO task (Watanabe et al, 2021). On the other hand, tSMS over the left DLPFC decreased performance in a working memory n-back task without affecting the reaction times (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these promising findings, some papers reported null effects of tDCS [ 163 , 164 , 165 , 166 , 167 ] and rTMS [ 168 , 169 , 170 ], and TBS research is still in its early stage, showing the need for further research and systematic reviews of the literature to consolidate results and address inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%